Reassessment and division of the genus Agraecia Audinet-Serville (Orthoptera: Tettigoniidae: Conocephalinae: Agraeciini) - Chamorro-Rengifo, Juliana; Braun, Holger; Lopes-Andrade, Cristiano (Zootaxa, 2015)
Agraecia Audinet-Serville, the type-genus of Agraeciini, comprises fifteen species names: thirteen used for extant species, one junior synonym, and one fossil. The species are morphologically very dissimilar, and were collected and described from different localities of the world. The genus was reassessed based on recently collected specimens from Brazil and Argentina as well as museum specimens. Based on morphological characteristics we re-delimit Agraecia sensu novo, keeping only two of the previously assigned species: A. punctata Saint-Fargeau & Audinet-Serville and A. dorsalis Karny. The subtribe Agraeciina subtrib. nov. is defined, which include Agraecia s. nov. and three new genera (Iaratrox Chamorro-Rengifo & Lopes-Andrade gen. nov., Starkonsa Chamorro-Rengifo & Lopes-Andrade gen. nov., and Yvelinula Chamorro-Rengifo & Lopes-Andrade gen. nov.). Three additional genera treated here, Parasubria Karny, Ragoniella Chamorro-Rengifo & Lopes-Andrade gen. nov., Redtenbachus Chamorro-Rengifo & Lopes-Andrade gen. nov. and Sylvainhugiella Chamorro-Rengifo & Lopes-Andrade gen. nov. currently remain unclassified inside Agraeciini. We desig-nate a neotype and describe the female and male for A. punctata. Bertoniella Rehn is proposed as a junior synonym of Agraecia, and Parasubria ziczac Karny as syn. nov. of Parasubria vittipes (Redtenbacher) comb. nov. The fossil species is transferred to Senexefigia† Chamorro-Rengifo & Lopes-Andrade gen. nov. We also describe two new species of Iaratrox gen. nov., I. brasilienses Chamorro-Rengifo & Lopes-Andrade sp. nov. and I. longicornia Chamorro-Rengifo & Lopes-Andrade sp. nov. The holotype of Agraecia fallax Karny nomen dubium seems to be lost and the syntypes of Agraecia festae Griffini are currently unavailable for examination, therefore, these two species are treated as incertae sedis, and should probably be transferred. A key to the studied genera is provided, as well as a key to species of Agraecia s. nov. and Iaratrox gen. nov. The calling songs of Parasubria vittipes (Redtenbacher) comb. nov. and Ragoniella pulchella (Hebard) comb. nov. are described. Numerous morphological details and some natural history aspects are discussed.